International political economy : perspectives on global power and wealth - Frieden, Jeffry A.; Lake, David A. (Routledge, 2000)
Now in its fourth edition, this best-selling reader in international political economy offers 31 solid articles - 15 new - by renowned scholars in political science and economics.
Keywords: International economic relations.; BUSINESS & ECONOMICS -- International -- General.; BUSINESS & ECONOMICS -- International -- Economics.; International economic relations